Best practices for Instagram in medical education: a study with randomized post designs - Wurm-Kuczera, Rebecca; König, Julia; Büntzel, Judith (In vivo, 2025)
Background/Aim: Instagram is a widely used visual communication platform with over one billion global users. Its visual and interactive features suggest potential for use in medical education, particularly for asynchronous learning. - Materials and Methods: To evaluate effective strategies for account promotion, content design, and outcome measurement, we launched the Instagram account “ilearnonco2021” during a hematology and medical oncology teaching module. Educational posts were uploaded according to a randomized controlled protocol. Post engagement was assessed using ‘likes’ as a surrogate marker for student interest. These assumptions were cross-validated through a post-course survey assessing students’ content preferences. - Results: Of 126 enrolled students, 49 (38.9%) subscribed to the account, with the majority recruited following a personalized email and references in the online study guide. Single-slide posts received a similar number of likes as multi-slide posts. Combining clinical trial content with supplementary visuals (e.g., comics, mnemonics, images) did not significantly increase engagement compared to single-slide trial posts. Posts in the category “mnemonics” received significantly more likes than clinical trial posts (p=0.01). Compared to a prior cohort, the current group showed a significantly lower rate of engagement, measured in likes per follower and post. - Conclusion: Instagram may serve as a supportive tool for asynchronous learning in medical education. However, its capacity to increase interest in clinical research appears limited. While ‘likes’ can indicate trends in engagement, they should be cross-validated with independent user surveys to ensure reliability.
Gesehen am 17.02.2026
Online veröffentlicht: 17. Juli 2025